2009
DOI: 10.1108/02651330910960799
|View full text |Cite
|
Sign up to set email alerts
|

Social marketing campaigns aimed at preventing drunk driving

Abstract: PurposeThe purpose of this paper is to examine the role of social marketing programs in preventing drunk driving, and how protection motivation theory (PMT) can be used to create effective anti drunk driving communications.Design/methodology/approachCommunication and program materials aimed at reducing drunk driving were identified and gathered from English‐language websites from the USA, Canada, UK, Australia, and New Zealand, and a qualitative review was conducted.FindingsThe review provides a description of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 30 publications
0
33
0
1
Order By: Relevance
“…More recently, PMT has been applied to other fields of study including environmental topics and personal safety (Cismaru and Lavack 2010;Cismaru et al 2009;Floyd et al 2000). PMT is a theory that employs a persuasive technique based on arousing fear in the target audience due to some proposed threat and subsequently, exploiting their desire to cope with or avoid the proposed threat.…”
Section: Current Water Management Campaignsmentioning
confidence: 99%
“…More recently, PMT has been applied to other fields of study including environmental topics and personal safety (Cismaru and Lavack 2010;Cismaru et al 2009;Floyd et al 2000). PMT is a theory that employs a persuasive technique based on arousing fear in the target audience due to some proposed threat and subsequently, exploiting their desire to cope with or avoid the proposed threat.…”
Section: Current Water Management Campaignsmentioning
confidence: 99%
“…Increasingly, however, the notion that celebrities can market ideas and model positive lifestyle behaviors has become accepted and useful in applications such as social marketing (e.g., Cismaru, Lavack, & Markewich, 2009;DeBar et al, 2009) and the dissemination of health information messages through television soap operas (Dutta-Bergman, 2006). Fetal development research stemming from what was originally known as the Barker hypothesis points to the intrauterine environment as a critical time, not only for the neonatal and infancy period, but as a factor that may affect a baby's health much later in life (Barker & Clark, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In order to ensure consistency in our interpretation, only social marketing interventions created by English‐speaking countries were included in the study. Several earlier studies have focused on a similar comparison analysis, such as content analyses of drink‐driving campaigns (Cismaru et al ., ), and of social marketing campaigns aimed at moderating alcohol intake among young people (Cismaru et al ., ). The third criterion, the presence of a video advertisement, was set because of the fact that in comparison with print advertisements and Internet sites, video advertisements reach a broader audience and are widely available on the Internet.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have demonstrated that social marketing campaigns aimed at preventing harmful drinking behaviours can be effective in addressing this problem (Yanovitzky & Stryker, 2001;Gordon, McDermott, Stead, & Angus, 2006;Hastings & McDermott, 2006). As the application of social marketing to the design and implementation of campaigns that aim to minimise problems caused by alcohol consumption has increased in popularity and use within the public health sector (Glider & Midyett, 2001;Grier & Bryant, 2005;Cismaru, Lavack, & Markevich, 2009;Tay, 2005), this research focuses specifically on the communication aspect of social marketing in the form of social marketing advertising (Arthur & Quester, 2003).…”
Section: Introductionmentioning
confidence: 99%